Adaptive Traditionalism in Islamic Politics: The Political Thoughts of KH. Wahab Chasbullah and the Transformation of Nahdlatul Ulama's Strategy - Kusuma, Ayusia Sabhita; Darmawan, Arief Bakhtiar; Marwan, Nurul Huda (POLITEA, 2026)
Islamic traditionalism is often portrayed as a static and conservative orientation that resists socio-political change and modern political engagement. This article examines the political thought of KH. Wahab Chasbullah and its role in shaping Nahdlatul Ulama's (NU) strategic responses to the changing dynamics of Indonesian politics. Employing a qualitative library research design with a historical-interpretive approach, this study analyzes KH. Wahab's political ideas through the concepts of Islamic traditionalism and pragmatic conservatism. The findings demonstrate that Wahab developed an adaptive form of Islamic traditionalism—an approach that seamlessly integrated religious authority with modern organizational and political strategies. Rather than rejecting change, his pragmatic conservatism enabled NU to preserve its religious traditions while responding strategically to shifting political configurations and state structures. The article therefore challenges the notion of Islamic traditionalism as a form of static conservatism and argues that adaptive traditionalism can function as a mode of political action that sustains religious continuity while facilitating organizational and political transformation.